THE CURRENT STATE OF DEVELOPMENT OF UNMANNED AERIAL SYSTEMS IN THE STRATOSPHERE - Kharchenko, Volodymyr; Onishchenko, Alexander (Proceedings of National Aviation University (archive), 2020)
This paper considers the main goals and objectives that are solved with the help of Unmanned Aerial Vehicles. The classification of modern Unmanned Aerial Vehicles (UAVs) by weight, altitude and flight duration is shown. Basic advantages and disadvantages of the UAVs use in a stratosphere are analysed in comparison with piloted aircraft